In this article, we will explore:
Before diving into rationalization, it’s important to have a solid understanding of adding, subtracting, multiplying, dividing, and simplifying surds. If you’re unfamiliar with these concepts, reviewing them first is recommended.
They are very important in practicing questions for Algebra as well.
Here is one more link to practice a few extra questions: Maths Genie Rationalising Surds Questions
Why Rationalize the Denominator?
Steps:
Step 1: Identify the surd in the denominator.
Step 2:Multiply both the numerator and the denominator by this surd.
Step 3:Simplify the resulting expression.
Solved Example
Question: Rationalize the denominator of: 5/√6
Solution:
Step 1: Multiply the numerator and the denominator by √6.
Step 2: Write the simplified expression.
Result: 5√6/6
Now, the denominator is rational, and the expression is rationalized.
Solved Example
Question: Rationalize the denominator of: 7/√5
Solution:
Step 1: Multiply the numerator and the denominator by √5.
Step 2: Simplify the expression.
Result: 7√5/5
Solved Example
Question: Rationalize the denominator of: 3/2√3
Solution:
Step 1: Multiply the numerator and the denominator by √3.
Step 2: Simplify the expression.
Step 3: Simplify the fraction.
Final Result: √3/2 (since 3/6 = 1/2)
What Is a Conjugate?
Steps:
Step 1: Identify the conjugate of the denominator.
Step 2: Multiply both the numerator and the denominator by the conjugate.
Step 3: Simplify the numerator and the denominator.
Step 4: Simplify the entire expression, if possible.
Solved Example
Question: Rationalize the denominator of: 5/(√6 + 3).
Solution:
Step 1: Identify the conjugate of the denominator.
Step 2: Multiply the numerator and the denominator by the conjugate.
Step 3: Simplify by dividing the numerator by -3.
Final Result: -5√6/3 + 5
Solved Example
Question: Rationalize the denominator of: 2/(3 – √2)
Solution:
Step 1: Conjugate of the denominator: 3 + √2.
Step 2: Multiply the numerator and the denominator by the conjugate.
Final Answer: (6 + 2√2)/7
Step 1: Identify the Denominator and Determine Its Conjugate:
Step 2: Multiply Numerator and Denominator by the Conjugate:
Step 3: Apply the Difference of Squares in the Denominator:
Step 4: Simplify the Numerator:
Step 5: Simplify the Entire Expression:
Solved Example
Question: Simplify: (√7 − 6)²
Solution:
This is equivalent to (√7 − 6) × (√7 − 6)
Apply the FOIL method.
Step 1: Multiply the First terms.
Step 2: Multiply the Outside terms.
Step 3: Multiply the Inside terms.
Step 4: Multiply the Last terms.
Step 5: Combine like terms.
Conclusion Expanding surds using double bracket multiplication is a vital skill for rationalizing denominators and solving complex surd problems.
By mastering this technique, you’ll be well-prepared to tackle exam questions involving surds. Remember to:
• Simplify surds when possible.
• Apply the FOIL method systematically.
• Combine like terms carefully.
Question 1: Simplify: (√2 + 5) × (√2 + 3)
Question 2: Simplify: (3√3 − 2) × (√3 + 4)
Question 3: Simplify: (2 + √5)²
Question 4: Simplify: (√6 − 4)(√6 + 4)
Question 5: Simplify: (5 + 2√3)(5 − 2√3)
Question 6: Simplify: (√7 + √2)(√7 − √2)
Question 7: Simplify: (3√2 + 4)(3√2 − 4)
Question 8: Simplify: (√3 + √5)²
Question 9: Simplify: (2√5 + 3√2)(2√5 − 3√2)
Question 10: Simplify: (√2 + √3)²
Question 1: Simplify: (√2 + 5) × (√2 + 3)
Answer:
Step 1: Multiply the First terms.
√2 × √2 = 2
Step 2: Multiply the Outside terms.
√2 × 3 = 3√2
Step 3: Multiply the Inside terms.
5 × √2 = 5√2
Step 4: Multiply the Last terms.
5 × 3 = 15
Step 5: Combine like terms.
3√2 + 5√2 = 8√2
2 + 15 = 17
Final Answer: 17 + 8√2
Question 2: Simplify: (3√3 − 2) × (√3 + 4)
Answer:
Step 1: Multiply the First terms.
3√3 × √3 = 9
Step 2: Multiply the Outside terms.
3√3 × 4 = 12√3
Step 3: Multiply the Inside terms.
(−2) × √3 = −2√3
Step 4: Multiply the Last terms.
(−2) × 4 = −8
Step 5: Combine like terms.
12√3 − 2√3 = 10√3
9 − 8 = 1
Final Answer: 1 + 10√3
Question 3: Simplify: (2 + √5)²
Answer:
This is equivalent to (2 + √5) × (2 + √5)
Step 1: Multiply the First terms.
2 × 2 = 4
Step 2: Multiply the Outside terms.
2 × √5 = 2√5
Step 3: Multiply the Inside terms.
√5 × 2 = 2√5
Step 4: Multiply the Last terms.
√5 × √5 = 5
Step 5: Combine like terms.
2√5 + 2√5 = 4√5
4 + 5 = 9
Final Answer: 9 + 4√5
Question 4: Simplify: (√6 − 4)(√6 + 4)
Answer:
Step 1: Calculate a²
(√6)² = 6
Step 2: Calculate b²
4² = 16
Step 3: Subtract b² from a²
6 − 16 = −10
Final Answer: −10
Question 5: Simplify: (5 + 2√3)(5 − 2√3)
Answer:
Using (a + b)(a − b) = a² − b²
Step 1: Calculate a²
5² = 25
Step 2: Calculate b²
Step 3: Subtract b² from a²
25 − 12 = 13
Final Answer: 13
Question 6: Simplify: (√7 + √2)(√7 − √2)
Answer:
Using (a + b)(a − b) = a² − b²
Step 1: Calculate a²
(√7)² = 7
Step 2: Calculate b²
(√2)² = 2
Step 3: Subtract b² from a²
7 − 2 = 5
Final Answer: 5
Question 7: Simplify: (3√2 + 4)(3√2 − 4)
Answer:
Using (a + b)(a − b) = a² − b²
Step 1: Calculate a²
Step 2: Calculate b²
4² = 16
Step 3: Subtract b² from a²
18 − 16 = 2
Final Answer: 2
Question 8: Simplify: (√3 + √5)²
Answer:
Equivalent to (√3 + √5) × (√3 + √5)
Step 1: Multiply the First terms.
√3 × √3 = 3
Step 2: Multiply the Outside terms.
√3 × √5 = √15
Step 3: Multiply the Inside terms.
√5 × √3 = √15
Step 4: Multiply the Last terms.
√5 × √5 = 5
Step 5: Combine like terms.
√15 + √15 = 2√15
3 + 5 = 8
Final Answer: 8 + 2√15
Question 9: Simplify: (2√5 + 3√2)(2√5 − 3√2)
Answer:
Using (a + b)(a − b) = a² − b²
Step 1: Calculate a²
Step 2: Calculate b²
Step 3: Subtract b² from a²
20 − 18 = 2
Final Answer: 2
Question 10: Simplify: (√2 + √3)²
Answer:
Equivalent to (√2 + √3) × (√2 + √3)
Step 1: Multiply the First terms.
√2 × √2 = 2
Step 2: Multiply the Outside terms.
√2 × √3 = √6
Step 3: Multiply the Inside terms.
√3 × √2 = √6
Step 4: Multiply the Last terms.
√3 × √3 = 3
Step 5: Combine like terms.
√6 + √6 = 2√6
2 + 3 = 5
Final Answer: 5 + 2√6